A model for measuring passenger loyalty - Skačkauskienė, Ilona; Vilkaitė-Vaitonė, Neringa; Raudeliūnienė, Jurgita; Davidavičienė, Vida (Transport, 2016)
Loyalty development is an essential condition for an increase in profit of airline, railway and road transport companies. It is undoubtedly relevant to the success of an organisation. However, there is a lack of unified and universally accepted indicators for customer loyalty. Consequently, a model for measuring customer loyalty can be barely applied to companies that provide transport services for passengers. This gap has presupposed the need to create a customer loyalty model that corresponds to modern needs of passenger transport organisations. The model needs to be flexible to be used by various transport organisations that provide services to passengers. Principal solutions for the design of a model for loyalty measurement emerged from the clarified role of passenger loyalty and evaluation problems. The worked out solutions include a selection of a proper concept (1), loyalty specification (2), and differentiation of loyalty measurement depending on accessible data (3). To measure loyalty, an informative and practical concept of loyalty has been chosen. Subsequently, a complex of indicators that correspond with features of passenger transport services was compiled and the measurement of customer loyalty was differentiated according to the situations of data accessibility. A quantitative model of passenger loyalty measurement is based on a behavioural concept and miscellaneous content. Therefore, it creates presumptions about measuring the state of passenger loyalty and choosing proper solutions for the development of passenger loyalty in transport organisations. First published online: 09 Oct 2015